Unique, Shared, and Dominant Brain Activation in Visual Word Form Area and Lateral Occipital Complex during Reading and Picture Naming. (15th January 2022) - Neudorf, Josh; Gould, Layla; Mickleborough, Marla J.S.; Ekstrand, Chelsea; Borowsky, Ron
Highlights: Explicitly defined unique, shared, and dominant fMRI brain activation Used familiar regular and exception words (and pictures) to force lexical reading When visual complexity is controlled, some dominant LOC activation for pictures Shared activation in VWFA and LOC for both reading and picture identification Challenges overly specialized models of reading or picture naming Abstract: Identifying printed words and pictures concurrently is ubiquitous in daily tasks, and so it is important to consider the extent to which reading words and naming pictures may share a cognitive-neurophysiological functional architecture. Two functional magnetic resonance imaging (fMRI) experiments examined whether reading along the left ventral occipitotemporal region (vOT; often referred to as a visual word form area, VWFA) has activation that is overlapping with referent pictures (i.e., both conditions significant and shared, or with one significantly more dominant ) or unique (i.e., one condition significant, the other not), and whether picture naming along the right lateral occipital complex (LOC) has overlapping or unique activation relative to referent words. Experiment 1 used familiar regular and exception words (to force lexical reading) and their corresponding pictures in separate naming blocks, and showed dominant activation for pictures in the LOC, and shared activation in the VWFA for exception words and their corresponding pictures (regular words did not elicit significant VWFA activation). Experiment 2 controlled for visual complexity by superimposing the words and pictures and instructing participants to either name the word or the picture, and showed primarily shared activation in the VWFA and LOC regions for both word reading and picture naming, with some dominant activation for pictures in the LOC. Overall, these results highlight the importance of including exception words to force lexical reading when comparing to picture naming, and the significant shared activation in VWFA and LOC serves to challenge specialized models of reading or picture naming.